Live Performance Characteristics, Pathogen Load and Foot Pad Lesions in Range-Reared Heritage vs. Conventional Turkeys (Meleagris gallopavo) - McCrea, B.A.; Leslie, M.A.; Stevenson, L.M.; Macklin, K.S.; Bauermeister, L.J.; Hess , J.B. (International Journal of Poultry Science, 2012)
A study was performed to compare the performance of heritage (Bourbon Red) and conventional (Broad Breasted White) turkey varieties in an outdoor range management system in the Southeastern United States. Turkeys were brooded indoors to 4 weeks of age and then moved to outdoor pens until processed at 17 weeks of age. Period and cumulative BW gain, feed intake and feed conversion were compared at 7, 10, 13 and 17 weeks of age. The final live weight, carcass weight and carcass yield were compared for both varieties and sexes of turkeys. Foot pad lesions were scored at 4, 7, 10, 13 and 17 weeks of age. The presence of Salmonella, Campylobacter, Clostridium perfringens, total aerobes and total enteric counts were determined via cloacal swabs or carcass rinsate. Significant differences between varieties with regard to live performance and carcass data were noted. The BBW turkeys had a higher feed intake, weight gain, live weights, carcass weights and carcass yields than the BR turkeys. Significant differences between the sexes for live weight and carcass weight but not carcass yield were also noted. Foot pad lesions were often identified in the BBW strain, with the majority of the BBW turkeys (75.2%) having detectable lesions by week 17. In comparison, the BR turkey had no lesions at week 17. The pathogen load of the two varieties was not different with the exception of Clostridium perfringens and total anaerobic counts, both of which were higher in BBW. The data collected in this study will aid small producers with alternative production of heritage turkey varieties.